The Impact of Intolerant Attitudes on Radical Preaching Behavior in Indonesia - Damansara, Ozan; Hasanah, Hilmatul; Hidayat, Akmal; Huda, Muhammad Khasanul; Qomariyah, Qomariyah (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2025)
This study aims to examine the relationship between intolerant attitudes and the tendency toward radical preaching behavior in Indonesia. In a multicultural society, intolerance can trigger the emergence of exclusive and unwelcoming religious narratives. This research employs a qualitative descriptive approach using literature review as the primary method of data collection. Data were gathered from academic literature, institutional reports, and relevant media documentation. The analysis reveals that intolerant attitudes, characterized by the rejection of diversity and an absolutist view of religious truth, have a strong potential to encourage radical preaching behavior. Such preaching is marked by hostile rhetoric, rejection of pluralism, and the marginalization of other groups. These findings highlight the urgency of promoting inclusive, moderate, and tolerant preaching practices as a strategy to curb the spread of religious radicalism in society.